2017
DOI: 10.14814/phy2.13398
|View full text |Cite
|
Sign up to set email alerts
|

Nfib hemizygous mice are protected from hyperoxic lung injury and death

Abstract: Nuclear Factor I (Nfi) genes encode transcription factors essential for the development of organ systems including the lung. Nfib null mice die at birth with immature lungs. Nfib hemizygous mice have reduced lung maturation with decreased survival. We therefore hypothesized that these mice would be more sensitive to lung injury and would have lower survival to hyperoxia. Adult Nfib hemizygous mice and their wild‐type (Wt) littermates were exposed to 100% O2 for 89, 80, 72 and 66 h for survival studies with lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…In human volunteers, breathing 95% oxygen for 17 h is associated with detectable increases in alveolocapillary permeability ( 15 ). Histologically, hyperoxia drives progressive destruction of alveolocapillary membranes leading to enlargement of air spaces, alveolar hemorrhage, and vascular network remodeling ( 28 , 32 ). Regression of lung capillary network (capillary rarefaction) has been demonstrated angiographically and histologically and is a result of the destruction of alveolocapillary membranes, obstruction of capillaries by microthrombi, and vascular pruning ( 27 , 40 , 46 ).…”
Section: Evolution Of Hyperoxic Lung Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…In human volunteers, breathing 95% oxygen for 17 h is associated with detectable increases in alveolocapillary permeability ( 15 ). Histologically, hyperoxia drives progressive destruction of alveolocapillary membranes leading to enlargement of air spaces, alveolar hemorrhage, and vascular network remodeling ( 28 , 32 ). Regression of lung capillary network (capillary rarefaction) has been demonstrated angiographically and histologically and is a result of the destruction of alveolocapillary membranes, obstruction of capillaries by microthrombi, and vascular pruning ( 27 , 40 , 46 ).…”
Section: Evolution Of Hyperoxic Lung Injurymentioning
confidence: 99%
“…Regression of lung capillary network (capillary rarefaction) has been demonstrated angiographically and histologically and is a result of the destruction of alveolocapillary membranes, obstruction of capillaries by microthrombi, and vascular pruning ( 27 , 40 , 46 ). The loss of the proportion of functional microcapillaries is accompanied by marked dilation and congestion of remaining vessels and diversion of blood flows (and whole cardiac output) through these remaining larger vessels, leading to pulmonary hypertension and intrapulmonary shunting ( 28 , 32 ).…”
Section: Evolution Of Hyperoxic Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that one of the likely cells of origin of SCLC is a rare neuroendocrine (NE) cell ( Gazdar et al., 1980 , Park et al., 2011 , Sutherland et al., 2011 ). NE cells are located throughout the pulmonary tree and can be found either as single cells or in clusters called NE bodies ( Kumar et al., 2017 , Kuo and Krasnow, 2015 ). Because human SCLC is often diagnosed late in the course of the disease, computed tomography (CT) scans of SCLC patients often reveal a bulky central mass with lymph node (LN) involvement, which makes the identification of primary tumor origin difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on Nfib -deficient mice have shown that loss of Nfib results in perinatal lethality due to lung maturation defects along with severe callosal agenesis and forebrain defects ( 21 ). Even Nfib hemizygous mice show reduced lung maturation and decreased survival ( 22 , 23 ). Dorsal telencephalon-specific Nfib conditional knockout mice show an obvious increase in cortical size ( 12 ), which may explain the macrocephaly observed in NFIB -deficient patients.…”
Section: Discussionmentioning
confidence: 99%